2006
DOI: 10.1007/s00464-005-0247-x
|View full text |Cite
|
Sign up to set email alerts
|

Proton pump inhibitors reduce gallbladder function

Abstract: Short-term PPI therapy reduces gallbladder motility in healthy volunteers. Chronic PPI therapy may pose a risk for long-term gallbladder dysfunction and biliary complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 20 publications
(21 reference statements)
2
22
0
2
Order By: Relevance
“…In a crossover study design in healthy individuals, PPI administration reduced the mean gallbladder ejection fraction from 56.4% ± 30.0% to 42.8% ± 32.3% ( P < 0.01) as measured using CCK-hepatobiliary iminodiacetic acid scans [ 46 ]. The number of patients with a gallbladder ejection fraction of less than 35%, traditionally used as the cutoff for acalculous cholecystitis, doubled to more than 50% of patients with PPI use.…”
Section: Gallbladder Functionmentioning
confidence: 98%
“…In a crossover study design in healthy individuals, PPI administration reduced the mean gallbladder ejection fraction from 56.4% ± 30.0% to 42.8% ± 32.3% ( P < 0.01) as measured using CCK-hepatobiliary iminodiacetic acid scans [ 46 ]. The number of patients with a gallbladder ejection fraction of less than 35%, traditionally used as the cutoff for acalculous cholecystitis, doubled to more than 50% of patients with PPI use.…”
Section: Gallbladder Functionmentioning
confidence: 98%
“…However, the effects of PPIs on small bowel motility or transit are unclear; it is known that PPIs produce a dose-dependent delay in gastric emptying [10]. Investigators have previously shown that one month of PPI therapy was associated with reduced gallbladder motility [16]. This may show that PPIs reduce gallbladder motility and cause gallstones.…”
Section: Discussionmentioning
confidence: 99%
“…Pallotta et al [20] documented the relationship of persistent gastrointestinal symptoms and delayed gastric emptying in dyspeptic patients. Cahan et al [21] showed that PPI therapy may be a causative factor in depressing digestive output.…”
Section: Discussionmentioning
confidence: 99%